2012
DOI: 10.1016/j.neuron.2012.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Control of Linear and Supralinear Dendritic Excitation in CA1 Pyramidal Neurons

Abstract: The transformation of dendritic excitatory synaptic inputs to axonal action potential output is the fundamental computation performed by all principal neurons. We show that in the hippocampus this transformation is potently controlled by recurrent inhibitory microcircuits. However, excitatory input on highly excitable dendritic branches could resist inhibitory control by generating strong dendritic spikes and trigger precisely timed action potential output. Furthermore, we show that inhibition-sensitive branch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
116
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(125 citation statements)
references
References 56 publications
8
116
1
Order By: Relevance
“…The ripple-frequency range is determined by experimentally measured characteristics of nonlinear dendrites (Ariav et al, 2003;Müller et al, 2012) and agrees with the experimentally found one. Slow dendritic spikes in the interneurons may also enable or contribute to ripplefrequency oscillations (Chiovini et al, 2014).…”
Section: Models For Spw/rssupporting
confidence: 83%
See 4 more Smart Citations
“…The ripple-frequency range is determined by experimentally measured characteristics of nonlinear dendrites (Ariav et al, 2003;Müller et al, 2012) and agrees with the experimentally found one. Slow dendritic spikes in the interneurons may also enable or contribute to ripplefrequency oscillations (Chiovini et al, 2014).…”
Section: Models For Spw/rssupporting
confidence: 83%
“…The resulting inhibitory feedback does not hinder the generation of dendritic spikes, but it decreases the probability that a somatic spike is initiated by hyperpolarization of the postsynaptic neurons (cf. Müller et al, 2012). As a consequence, for very large synchronous pulses, the inhibitory feedback overwhelms the excitation, the pulse does not spread further across the network, and the overall activity decays to the level of spon- frac of place cells that spike at least once during the replay events.…”
Section: Replay and Emergence Of Spw/r-like Eventsmentioning
confidence: 99%
See 3 more Smart Citations